The ethics of responsibility within oncologic gynaecology - Di Pietro, Maria Luisa; Sgreccia, Elio (Medicina e Morale, 1999)
Gynaecologic neoplastic pathologies always represent a time of responsibility and worry for both patients and physicians. Besides the patient's fear of having cancer and the uncertainty of therapy results, there is the pain of going through the mutilation of organs that are considered crucial for the structure and the acknowledgement of women's identity, and there is the consequent inability to procreate or the difficulty - if the woman is pregnant - to bring pregnancy to an end. Bioethical literature deals with the hard and conflicting situations that patients and physicians must face, with special reference to principlism does often sharpen, rather than solve, the situation of conflict, especially in this case, when the rights to be defended are not only the physician's and the mother's ones, but also the foetus', if the woman is pregnant. For this reason, the Authors suggest the reference to the ethical category of responsibility, according to which the autonomy of patients and physicians matches with the good they are born from and they live for. Within gynaecologic oncology, the ethics of responsibility is involved at least in three cases: prevention, therapeutic choice, health care.